Dynamics of Tourism Development in Geosite, Gunungsewu Geopark - Primantoro Nur Vitrianto; Wiendu Nuryanti; Dwita Hadi Rahmi (Goodwood Publishing, 2021)
Purpose: The designation of the Gunungsewu UNESCO Global Geopark has implications for the development of various tourism destinations. This article seeks to reveal how the development of the Gunungsewu geopark in Gunungkidul district as a tourism destination. Methods: This study uses a qualitative method. The data used were descriptive data, with in-depth analysis. Collecting samples through proportional sampling, the selection of samples depends on the purpose of the study without regard to the ability of a generalist. Results: The level of development of tourism destinations in mountain geoparks varies based on Butler's classification of tourism destination development. Determination of an area with unique geomorphology cannot simultaneously lift the entire area into a tourist destination. Limitation: This study focuses on developing a geosite seen as a tourism destination. This study emphasizes observing the development of tourism destinations using the “Tourism Area Life Cycle” approach proposed by Butler (1980). Contribution: This research is expected to benefit the development of tourism science and geoparks in Indonesia. Conclusion: Species diversity in the Protection Report Diary (in 2010) was higher compared to the total number of wildlife species sighted by visitors (in 2021) and during the patrol (in 2020) indicating that some wildlife species in LCC declined within 10 years.